The Impact of Regional Economic Growth and Investment on Unemployment in Indonesia - Ainul Mardhiah (one million dreams corporation, 2025)
Unemployment is a major employment issue faced by developing countries, including Indonesia. This study aims to analyze the influence of regional economic growth and investment on the unemployment rate in Indonesia. The study uses a quantitative approach with secondary data, in the form of panel data from 34 provinces from 2016–2020, sourced from the Central Statistics Agency (BPS). The analytical method used is panel data regression with a Random Effects Model. The results show that, partially, economic growth has a negative and significant effect on unemployment, while investment has a positive but insignificant effect. Simultaneously, both variables significantly influence unemployment. These findings provide implications for the government in designing policies to reduce unemployment by increasing quality economic growth and creating a conducive investment climate.